When the planet rages : natural disasters, global warming, and the future of the earth - Officer, Charles B.; Page, Jake.; Officer, Charles B. (Oxford ; New York : Oxford University Press, 2009)
"Charles Officer and Jake Page describe some of the great events of environmental history, from calamities such as the Lisbon earthquake of 1755 (the greatest in recorded history) and the centuries-long cycles of ice ages, to recent man-made disasters such as Chernobyl, acid rain, and the depletion of the ozone layer. Officer and Page provide discussions of meteorites and comets; of the demise of mammoths, mastodons, and dinosaurs; and of great floods that have swept the earth. But they also show that human activity can make trouble for nature, discussing the depletion of natural resources (we burn coal and oil at millions of times their natural rate of production), air pollution in Los Angeles and London (where the Killer Smog of 1952 caused the death of some four thousand people), and the pollution of major waterways, like the Chesapeake Bay and Lake Erie."--BOOK JACKET.
Preface to the revised edition -- Preface to the first edition -- pt. 1. Nature's effect on mankind -- 1. The earth is still hot and mobile -- Tambora : the year without a summer -- Laki : acid rain in Europe -- Krakatoa : colorful sunsets -- Santorini : the myth maker -- Toba, Yellowstone, and Long Valley : gigantic eruptions -- 2. ...And from time to time its surface moves around -- Haicheng and Tangshan : Chinese earthquakes and earthquake predictions -- San Francisco : earthquakes along the San Andreas fault and United States earthquake predictions -- New Madrid and Charleston : largest earthquakes in North America -- Lisbon : All Saints' Day in Portugal -- 3. There have been frequent flooding and sea-level change events on earth -- Gilgamesh : the flood -- Scablands : major flooding events -- New York and Miami : relative sea-level changes -- 4. ...And occasional visitors from outer space -- Halley's comet : our regular visitor -- Tunguska : meteor impacts -- pt. 2. Changes in climate and life on earth -- 5. The earth's climate changes on a variety of time scales -- Little Ice Age : advance and retreat of the glaciers -- Sahel : alternate drought and plenty in the sub-Sahara -- Historical temperature changes : ups and downs, whys and wherefores -- Ice ages : Milankovitch cycles or chaos theory -- Geologic climatic changes : temperature, oxygen, and carbon dioxide -- 6. ...And on rare occasions there are changes in its community of living things -- Pandemics : bubonic plague -- Ice ages : demise of woolly mammoth and cohorts -- Cretaceous/tertiary : the great dinosaur extinction controversy -- Other geologic extinctions : similarities and differences among the geologic extinction events -- pt. 3. Our effect on nature -- 7. Then along came us and we have effected vast environmental changes on a local and regional scale -- London and Los Angeles : smog -- Lake Erie and Chesapeake Bay : marine pollution -- Minamata : toxic wastes -- Chernobyl : nuclear wastes -- 8. ...With the potential for equally great changes on a global scale -- Ozone layer depletion : natural or anthropogenic? -- Acid rain : acid lakes and forest devastation -- Population growth : the major unaddressed problem -- Natural resources depletion : fossil fuels and minerals -- Carbon dioxide emissions : global warming or not? -- Global climate change -- 9. The most fundamental question facing mankind today is whether man can evolve to live in harmony with nature -- Environmental changes and times : geologic and human perspectives -- Environmental research : a catch-22 -- Local and global anthropogenic changes : where the problems are -- Epilogue : where do we go from here? -- References -- Index.
Rev. ed. of : Tales of the earth. New York : Oxford University Press, c1993.
Includes bibliographical references and index.
Keywords: Earth; Environmental degradation; Nature -- Effect of human beings on; Earth